THE ROLE OF THE OMBUDSMAN IN THE PROCESS OF EXECUTING A PRISON SENTENCE - Aleksandra Leszczyńska (Probacja)
The situation of persons deprived of their liberty is beyond any doubt special due to numerous factors. These are the acts they committed, the prison environment, social stigmatization, problems related to isolation, etc. These people often find it difficult to seek help from anyone. However, convicts have numerous rights. Pursuant to the Act, prisoners may benefit from the assistance of the Ombudsman in this respect. The article describes the role of the Ombudsman in the process of executing a prison sentence and its essence. This study presents examples of selected activities on this topic along with the author's observations.